Numerical investigation on the single phase forced convection heat transfer characteristics of TiO2 nanofluids in a double-tube counter flow heat exchanger - Demir, H.; Dalkilic, A. S.; Kurekci, N. A.; Duangthongsuk, W.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
In this study, forced convection flows of nanofluids consisting of water with TiO2 and Al2O3 nanoparticles in a horizontal tube with constant wall temperature are investigated numerically. The horizontal test section is modeled and solved using a CFD program. Palm et al.'s correlations are used to determine the nanofluid properties. A single-phase model having two-dimensional equations is employed with either constant or temperature dependent properties to study the hydrodynamics and thermal behaviors of the nanofluid flow. The numerical investigation is performed for a constant particle size of Al2O3 as a case study after the validation of its model by means of the experimental data of Duangthongsuk and Wongwises with TiO2 nanoparticles. The velocity and temperature vectors are presented in the entrance and fully developed region. The variations of the fluid temperature, local heat transfer coefficient and pressure drop along tube length are shown in the paper. Effects of nanoparticles concentration and Reynolds number on the wall shear stress, Nusselt number, heat transfer coefficient and pressure drop are presented. Numerical results show the heat transfer enhancement due to presence of the nanoparticles in the fluid in accordance with the results of the experimental study used for the validation process of the numerical model. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Heat transfer coefficient; Pressure drop; Wall shear stress; Nanofluid; Heat exchanger; TRANSFER ENHANCEMENT; THERMOPHYSICAL PROPERTIES; FLUIDS; Thermodynamics; Mechanics